Reliability Analysis of Unit HD 465-7R at Badiwata Site, PT. Sumber Mitra Jaya - Syahruddin Syahruddin (Jurnal Teknologi Terpadu, 2019)
This study aimed to determine the reliability and factors that influence the reliability of HD 465-7R units at the Badiwata Site of PT. Sumber Mitra Jaya. This study utilized field observation methods, document analysis from Historical Units, Monthly Physical Availability Heavy Equipment Reports, Key Performance Indicators and interviews. Data was processed using nonprobability sampling technique with purposive sampling method. Furthermore, it was analyzed by grouping data based on variables, classifying data types, tabulating data, presenting data and performing reliability calculations. To analyze quantitative data, descriptive statistics was used. Reliability measures include calculation of Mean Time To Repair (MTTF) and Mean Time Between Failure (MTBF). Data was presented in form of tables, histograms and pareto diagrams. It showed the reliability of the HD465-7R unit decreased every month. It was recorded 84% in August, 80% in September, and 75% in October.  Factors which influenced the reliability of the HD465-7R unit included the frequency of damage to tire, brake, accident and electrical problems.